Beta-alanine supplementation and anaerobic performance in highly trained judo athletes - Halz, M.; Kaszuba, M.; Helbin, J.; Krzysztofik, S.; Suchanecka, A.; Zajac, A. (Baltic Journal of Health and Physical Activity, 2022)
Introduction. Previous studies have shown that several weeks of beta-alanine (BA) supplementation increases anaerobic work capacity and decreases muscular fatigue, but limited research was conducted on elite martial arts athletes. Therefore, the purpose of this study was to investigate the effect of chronic BA supplementation on high-intensity intermittent upper and lower-body performance in highly-trained judo athletes. Material and Methods: Sixteen elite judo athletes (21.8 ± 2.5 years old) were randomly assigned to receive either BA (4 g/d over the first 2 weeks and 6 g/d in the last 2 weeks) or placebo for 4 weeks. Before and after BA supplementation, the athletes completed two double 30-s upper and lower limb Wingate tests, separated by 3 min. Blood samples were collected for lactate and di-carbonate concentration at baseline and post-exercise. Results: BA supplementation improved Lower and Upper Limb Total Work (p < 0.001) and Upper Limb Mean Power (p < 0.001) during Wingate Test. However, there were no significant differences in Lower Limb Mean Power in the BA group and in any obtained results in the placebo group. Additionally, a significant increase in the postworkout lactate and di-carbonate concentration (p < 0.001) was observed. Conclusions: Chronic supplementation of BA effectively enhances high-intensity intermittent upper and lower-body performance in highly-trained judo athletes.